Advances in Mucoadhesive Polymers and Formulations for Transmucosal Drug Delivery - Khutoryanskiy, Vitaliy (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Mucoadhesive polymers are widely used in the design of dosage forms for transmucosal drug delivery to the eye, respiratory, gastrointestinal and reproductive tracts. These routes of drug administration offer a number of advantages including improved drug bioavailability, reduced frequency of administration, and the avoidance for the use of injections.